THE ROLE OF SELF-CONFIDENCE IN MEDIATING THE EFFECT OF WORK DISCIPLINE AND REWARD TO EMPLOYEE PERFORMANCE IN PRIVATE COMPANIES IN SERANG DISTRICT - Sari, Juwita; Rustandi, Tata; Suadma, Udin (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
ABSTRACT Employee performance is a key factor in achieving company goals, and various factors such as work discipline and rewards play an important role in improving employee performance. Self-confidence is also considered a potential mediator in this relationship, but is still poorly understood in the context of private companies in Serang Regency. This research aims to examine the role of self-confidence in mediating the influence of work discipline and rewards on employee performance. The purpose of this research is to examine and analyze the influence of work discipline on employee performance, the influence of rewards on employee performance, the role of self-confidence as a mediator in the relationship between work discipline and employee performance. As well as the role of self-confidence as a mediator in the relationship between rewards and employee performance. This research uses a quantitative approach with a survey design. Data was collected from 190 employees of private companies in Serang Regency through a questionnaire whose validity and reliability were tested. Data analysis was carried out using path analysis techniques to test direct and mediation relationships. The research results show that work discipline and rewards have a significant positive influence on employee performance. Apart from that, self-confidence has been proven to partially mediate the influence of work discipline and rewards on employee performance. This mediation strengthens the relationship between these variables, showing that self-confidence is a key factor in improving employee performance. These findings indicate that increasing self-confidence among employees can strengthen the positive impact of work discipline and rewards on employee performance. Therefore, companies need to consider training and development programs that focus on increasing self-confidence as part of their human resource management strategy. This research contributes to the literature by emphasizing the importance of self-confidence as a mediator in the context of private companies in Indonesia.